The Political Challenge of Islamic Economic Development in The Jokowi Government, Indonesia - Dahlan, Ahmad; Voak, Adam; Aprianto, Naerul Edwin Kiky (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
The Jokowi administration which held two terms of parliament between 2014-2019 and 2019-2024 introduced what many believed were controversial policies around the development of Sharia financial frameworks, resulting in significant political discussion within Indonesia. With conflicts and robust grassroots challenges between the government and Islamic groups particularly preceding the 2019 election. This article aims to better understand the Jokowi government's support for the development of Sharia finance, as well as the strategies and policies implemented by his government in dealing with tensions with Islamic groups. This research deploys a historical analysis of literature during Jokowi’s two terms of government. The research interestingly reveals that the Jokowi government had indeed introduced a series of initiatives and platformed various master plan iterations to encourage and support the growth of Sharia finance in Indonesia. However, policy implementation challenges still prevail and may place real pressure on future governments to either roll back these initiatives or discard them completely. Yet, even given this political antecedence Jokowi's government has managed to initiate and deploy a Sharia finance master plan. Only time will tell, whether Indonesia can overcome many political challenges to continue on its new strategic Islamic-inspired economic path.